(untitled) (Agro Productividad, 2022)
Objective: The aim of this study was to test the survival of Macrobrachium tenellum in different confinement conditions with Dormitator latifrons. Design/methodology/approach: Using wild specimens acclimated to captive conditions of both species, three trials of different proportion were performed with treatments consisting in the presence/absence of food and shelters. Prawn/fish proportion for the assays were: 15/15 for T1, 15/3 for T2 and 10/3 for T3. In assays T1 and T2 juvenile prawns and fish were used, while in T3 post-larvae prawns and pre-juvenile fish were used. To test the survival with or without fed, it was schedule a four-day feeding ad libitum period, following by a two-day fed depravation period in all the assays. Results: In assays with juveniles of M. tenellum the survival rate was superior to 80% with or without shelter, when T1 showed 97-100% survival; meanwhile T3 presented a 56.67 % of survival, suggesting it’s necessary to use only juvenile prawns in co-culture systems. The use of shelters and fed deprivation had no significant effects on the survival of prawns. Limitations on study/implications: M. tenellum is an important aquatic resource for the central Mexican Pacific, region in which the D. latifrons is a representative native fish with a developing aquaculture. A polyculture or co-culture system with these species can accelerate the sustainability of both species productions. Findings/conclusions: The results suggest this polyculture system may be feasible, and longer duration culture are recommended.